National culture and corporate cash holdings around the world - Chen, Yangyang; Dou, Paul Y.; Rhee, S. Ghon; Truong, Cameron; Veeraraghavan, Madhu (Journal of banking & finance, 2015)
This paper examines whether cultural dimensions explain the variation in corporate cash holdings around the world as well as within the United States. We establish four major findings. First, in an international setting, corporate cash holdings are negatively associated with individualism and positively associated with uncertainty-avoidance. Second, individualism and uncertainty avoidance influence the precautionary motive for holding cash. Third, firms in individualistic states in the United States hold less cash than firms in collectivistic states. Fourth, we show that individualism is positively related to the firm’s capital expenditures, acquisitions, and repurchases while uncertainty avoidance is negatively related. Our findings remain unchanged after controlling for governance factors, firm attributes, and country characteristics.